Procedimentos para análise de lucratividade de produtos no setor de autopeças metálicas - Silva, Fabio Francisco da [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
In a globalized world, organizations face an increasingly dynamic, innovative and competitive environment, so that this condition requires continuous adaptation to market developments. Intense competition requires organizations to further improve their performance, making productive efficiency a key factor for survival. A methodology that has added value to the product through a reconfiguration of the production method is the implementation of a management philosophy called Lean Six Sigma. The main objective of this work is, in the light of the Lean Six Sigma philosophy, intervene in a critical-collaborative way to develop procedures for analyzing the profitability of products in a company specializing in steel processing. To achieve this goal, were applied the method of action-research to intervene in a group of professionals for the study of the profitability of products in a auto parts industry. The interaction of practical and theoretical knowledge provided by the action-research allowed the business program was enhanced. The procedures proposed in this study were able to identify the current profitability of the product, the main causes of inefficiency and productive for solutions to reduce production inefficiencies, when the productive systems planned and actual production system were compared. The results indicate that current profitability of -3%, while the parameter provided during budget was 10%. Thus, it is concluded that the low profitability of the products may compromise the company's financial results and affect their competitiveness in the market. To address this problem, the Lean Six Sigma presents itself as a versatile and high applicability philosophy, providing relevant results for characterization and troubleshooting. It was also observed that the evidence presented in this paper can be adapted to other companies in the metal auto parts segment to identify and recover the profitability of products

Em um mundo globalizado, as organizações enfrentam um ambiente cada vez mais dinâmico, inovador e competitivo, de modo que essa condição exige uma adaptação contínua à evolução do mercado. A competição intensa exige que as organizações aperfeiçoem seu desempenho, tornando a eficiência produtiva um fator fundamental para sobrevivência da empresa. Uma metodologia que tem agregado valor ao produto por meio de uma reconfiguração do método produtivo é a implantação da filosofia de gestão chamada Lean Seis Sigma. O objetivo principal desse trabalho é, à luz da filosofia Lean Seis Sigma, intervir de forma crítica-colaborativa na elaboração de procedimentos para análise da lucratividade de produtos em uma empresa especialista no processamento de aço. Para atingir o objetivo, foi aplicado o método de pesquisa-ação de caráter intervencionista em um grupo de profissionais destinados ao estudo da lucratividade de produtos de uma indústria de autopeças. A interação dos conhecimentos práticos e teóricos proporcionados pela pesquisa-ação permitiu que o programa empresarial fosse aprimorado. Assim, os procedimentos propostos neste trabalho foram capazes de identificar a lucratividade atual do produto, as principais causas da ineficiência produtiva e obter soluções para redução da ineficiência produtiva, quando comparados os sistemas produtivos previstos versus sistema produtivo real. Os resultados apontam uma lucratividade atual de -3%, enquanto que o parâmetro previsto na fase de orçamento era de 10%. Dessa forma, conclui-se que a baixa lucratividade dos produtos pode comprometer os resultados financeiros da empresa e afetar sua competitividade no mercado. Para enfrentar esse problema, o Lean Seis Sigma apresenta-se como uma filosofia versátil e de alta aplicabilidade, fornecendo resultados relevantes para caracterização e ... (Resumo completo, clicar no acesso eletrônico abaixo)
Keywords: Seis sigma (Padrão de controle de qualidade); Lucros; Automoveis - Peças; Controle de processo; Six sigma (Quality control standard)